Juridical Analysis of the Responsibility of Cosmetic Manufacturers for the Halal Needs of Muslim Consumers - Alfiyah, Siti; Mardikaningsih, Rahayu; Issalillah, Fayola (Bulletin of Science, Technology and Society, 2023)
The halalness of cosmetic products has become an essential aspect for Muslim consumers who seek products in accordance with their religious values. This research discusses the legal responsibilities of cosmetics manufacturers towards Muslim consumers, the impact of the absence of halal certification on purchasing decisions, as well as the steps needed to ensure their products are in accordance with halal principles. Using a normative juridical approach, this study evaluates relevant regulations, such as Law Number 33 Year 2014 on Halal Product Guarantee, as well as compares international standards to provide a comprehensive view. The analysis shows that the absence of halal certification can undermine the trust of Muslim consumers and affect their loyalty and purchasing decisions. Manufacturers are faced with legal and moral obligations to ensure transparency of production processes, compliance with halal standards, and truthful labeling. Strategic measures, such as raw material audits, employee training and continuous supervision, are needed to mitigate legal risks and create trust in the market. This study suggests the need for regulatory strengthening and harmonization of international halal standards to support producers and protect the rights of Muslim consumers.